Acute Abdominal Pain in Children: Causes and Development Factors - E. A. Romanova; L. S. Namazova-Baranova; E. Yu. Dyakonova; A. Yu. Romanov; K. S. Mezhidov; Z. I. Dokhshukaeva (Педиатрическая фармакология, 2017)
Currently differential diagnosis of acute abdominal pain syndrome in children at prehospital care units is vital and urgent problem which requires solution. Unfortunately, embarrassing mistakes are still followed by late or inadequate treatment and complications as a result. The problem solution requires both medical stuff alert and diagnosis algorithm revision and improvement. Improvement of technical equipment and availability of instrumental diagnostic methods at the out-hospital settings is a pressing need. The article provides a classification, detailed pathogenesis, and clinical presentation of acute abdominal pain in children under different nosologies (therapeutic and surgical). We considered the problem of adequate differential diagnosis of acute abdominal pain in children when the diagnostics is performed by primary care physicians and specialists of emergency medical services at the prehospital stage.